Human Herpesviruses (Advances in Experimental Medicine and Biology,, 2018)
This book introduces and reviews several topics for each human herpesvirus. One of the most important features of the book is that it covers aspects of both basic research and clinical medicine. Herpesviridae, a family of double-strand DNA viruses, has unique biological features by which these viruses establish latency after primary infection and reactivate in later life. Nine human herpesviruses are known so far, and each of them causes a variety of diseases in both primary infection and reactivation. Since the discovery of each human herpesvirus, an abundance of findings related to them has accumulated in basic research and clinical medicine. However, the vast majority of biological features is still masked in mystery. Furthermore, a strategy of treatment and prevention has not yet been established for most human herpesviruses. A wide range of readers will be interested in this volume with its treatment of problematic points and latest findings in the field.